2011
DOI: 10.1007/s10551-011-0967-x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Issues in Environmental Corporate Social Responsibility (ECSR): Toward a Transparent, Reliable, and Construct Valid Instrument

Abstract: One of the major roadblocks in conducting Environmental Corporate Social Responsibility (ECSR) research is operationalization of the construct. Existing ECSR measurement tools either require primary data gathering or special subscriptions to proprietary databases that have limited replicability. We address this deficiency by developing a transparent ECSR measure, with an explicit coding scheme, that strictly relies on publicly available data. Our ECSR measure tests favorably for internal consistency and inter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(154 citation statements)
references
References 54 publications
3
147
0
4
Order By: Relevance
“…Sixteen of these 25 firms had published CSR or annual reports that contain information on diversity management. Similar to Rahman and Post (2012), I found no discrepancies between the information on the 2012 reports and on the current webpages. These results thus suggested that both the 2012 annual reports and the information on the webpages are useful sources for collecting information on firms' diversity management practices for the full sample.…”
Section: Pilot Testingsupporting
confidence: 68%
See 1 more Smart Citation
“…Sixteen of these 25 firms had published CSR or annual reports that contain information on diversity management. Similar to Rahman and Post (2012), I found no discrepancies between the information on the 2012 reports and on the current webpages. These results thus suggested that both the 2012 annual reports and the information on the webpages are useful sources for collecting information on firms' diversity management practices for the full sample.…”
Section: Pilot Testingsupporting
confidence: 68%
“…Corporate websites are increasingly being validated as reliable instruments to collect information on companies' social, ethical, and environmental performance (Jose & Lee, 2007;RubaiiBarrett & Wise, 2007;Singh & Point, 2004). Furthermore, Rahman and Post (2012) found that the data disclosed by companies on their corporate websites are consistent with those found in their annual reports. However, given that information on a corporate website may not be formally audited, it will not be used to make any interpretation or conclusion about the firms' levels of commitment, but rather to reveal characteristics about the diversity and ethical practices of companies in this sample.…”
Section: Samplementioning
confidence: 94%
“…Previously presented studies primarily recognised the importance of CSR in large manufacturing enterprises and within the hotel (lodging) sector. To date, research findings into CSR in hotel industry have confirmed that if hotel organizations adopt and integrate CSR into their organizational strategies, they can facilitate innovativeness (Čivre and Gomezelj Omerzel 2015;Calveras 2015); increase and/or improve their organizational competitiveness (Kang et al 2015;Garay and Font 2012) and brand image (Tingchi et al 2014); boost employees' and customers' loyalty (García de Leaniz and Rodríguez Del Bosque Rodríguez 2015; Lee 2016); conserve environments (Rahman and Post, 2012), while at the same time contributing to solving problems in society that may arise (Smith and Ong 2015). According to Chen (2015) travellers are progressively more concerned with how tourist companies make their money and are expecting businesses to engage in responsible activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature has reviewed CSR practices extensively for the large manufacturing enterprises (Egri and Herman 2000;Epstein and Buhovac 2014;Hooghiemstra 2000;Ioannou and Serafeim 2015;Jamali 2008;Juščius and Snieška 2015;Rahman and Post 2012;Seifert et al 2004), yet there is little evidence from the service sector (Kang et al 2010; Lee and Heo 2009;Tzschentke et al 2008b), and even less for restaurant businesses (Chou et al 2012;Hu et al 2010;Perramon et al 2014). Further examination reveals that since 2005 a considerable amount of literature (Dodds and Joppe 2005;Golob and Bartlett 2007;Holcomb et al 2007; Lee and Heo 2009;Martínez et al 2014;Medrado and Jackson 2015;Reverte 2015) has grown up around the theme of promoting general and strategic guidelines for implementing CSR practices in tourism industry.…”
Section: Introductionmentioning
confidence: 99%
“…The literature offers many approaches to the measurement of company-disclosed CSR commitments (Rahman & Post, 2012;Font, Walmsley, Cogotti, McCombes, & Häusler, 2012;Bouten et al, 2011;Striukova, Unerman, & Guthrie, 2008;Beattie & Thomson, 2007;Guthrie & Abeysekera, 2006;Longo, Mura, & Bonoli, 2005). There are also numerous studies dealing with customer-perceived CSR (Pomering & Dolnicar, 2009;Ramasamy & Yeung, 2009;Luo & Bhattacharya, 2006;Becker-Olsen, Cudmore, & Hill, 2006;Meijer & Schuyt, 2005) and customer-required CSR (Adlwarth, 2010;Poolthong & Mandhachitara, 2009;Podnar & Golob, 2007;Dawkins & Lewis, 2003).…”
Section: Introductionmentioning
confidence: 99%